(untitled) (Mustansiria Dental Journal, 2018)
Successful treatment of molar furcation defects remains a challenge in clinical practice. Knowledge of anatomic factors facilitates predictable management of furcation involvement lesions. Intermediate bifurcational ridge (IBRs) and cementicles are of those anatomical variations which considered as problems in progression treatment of the disease. The present study was carried out to investigate the prevalence of IBRs and cementicles in Iraqi mandibular molars. The sample used in the study included 498 extracted mandibular molars. The results revealed that the prevalence IBRs was 306/498 teeth (61.44%), and that for the cementicles was 204/498 teeth (40.96%). The total sample was allocated into two groups: Group 1 included 313 molars (165 mandibular first molar and 148 mandibular second molar) , The teeth of group 1 were extracted because of caries and pulpal lesions, while Group 2 included 185 mandibular molars ( 98 first molar and 87 second molar). The reason of extraction of the teeth of group 2 was periodontal disease (different degrees of furcation involvement). For group 1 the results showed that 111/313 (35.46%) of mandibular molars had attached cementicles in furcation area and 185/313 (59.10%) were affected by IBRs. While in group 2 the percentage of both anomalies was higher than that of group 1. In group 2 the results revealed that 93/185 (50.27%) of the teeth had cementicles and 121/185 (65.4%) were recorded with IBRs. These results give an indication that the prevalence of cem. and IBRs high enough to be of clinical importance.